Temporal Order of Attentional Disengagement and Reengagement: Estimation with Steady-State Visual Evoked Potential - Satoshi Shioiri; Yoshiyuki Kashiwase; Kazumichi Matsumiya; Ichiro Kuriki (i-Perception, 2012)
An attention shift has been assumed to comprise three stages of neural processes: disengagement from the initially attended location, shift to a new destination, and reengagement on the new location. We developed a novel experimental paradigm to estimate the timings of attentional “disengagement” and “reengagement”. We recorded steady-state visual evoked potentials (SSVEPs) for two flickering stimuli at different frequencies, which were presented on the left and right of the center of the display. Participants were, after attending to the either stimulus, instructed to stay their attention on the same location, or to shift attention toward the other stimulus. We estimated the time course of attentional disengagement and that of attentional reengagement from the difference between the SSVEPs under different attention shift conditions. We conducted two experiments using exogenous (Experiment 1) and endogenous cues (Experiment 2) for controlling visual attention and succeeded to measure the time courses of SSVEP modulations accompanied by disengagement and reengagement of attention. Interestingly, temporal orders of the attentional processes differed between these experiments. In Experiment 1, attention was reengaged to a new object earlier than it was disengaged from the initially attended object. In Experiment 2, on the other hand, attentional reengagement occurred no significantly earlier than disengagement. These results suggest that attention shift processes were not executed in a fixed order; rather, the timings seem to change depending on the types of attention involved in the shift.